Effect of Fenton oxidation on biodegradability, biotoxicity and dissolved organic matter distribution of concentrated landfill leachate derived from a membrane process. (April 2015) - He, Ruo; Tian, Bao-Hu; Zhang, Qi-Qi; Zhang, Hong-Tao
Highlights: Toluene, ethylbenzene, chlorobenzene predominate in the hydrophilic (HyI) fraction. Phthalate esters are mainly absorbed on humic acid (HA), fulvic acid (FA) fractions. The biotoxicity of the DOM fractions to luminescent bacteria is HA > FA > HyI. Metals are the main toxic contributor to luminous bacteria in concentrated leachate. Abstract: The treatment of concentrated landfill leachate from membrane process is a troublesome issue due to high concentrations of biorecalcitrant pollutants. In this study, the effect of Fenton process on dissolved organic matter (DOM) distribution (i.e. humic acid (HA), fulvic acid (FA) and hydrophilic fraction (HyI)), chemical forms of toxic organic compounds and metals, and their biotoxicity were investigated. In the concentrated leachate, toluene, ethylbenzene and chlorobenzene predominated in the HyI fraction, while phthalate esters (PAEs) were mainly absorbed on the HA and FA fractions. PAEs were more readily removed from the HA and FA fractions than that from the HyI fraction in the Fenton process. The complexing abilities of DOM varied with types of metal in the concentrated leachate. The biotoxicities of the DOM fractions to luminescent bacteria ( Photobacterium phosphoreum T3 mutation) were HA > FA > HyI. The biotoxicities of the hydrophobic organic contaminants to luminescent bacteria were not obvious in the concentrated leachate due to their low concentrations. Metals might be the main contributor to the biotoxicity to luminous bacteria in the concentrated leachate. These results indicated that Fenton process could influence the pollutants distribution in DOM and their biotoxicities through the breakdown of HA and FA in the concentrated leachate.